Nâng cao hiệu quả cấp nước các đô thị - Phạm, Trí Minh (2011)
Tác giả: Phạm Trí Minh, KS; Bùi Đình Khoa, KS; Lưu Văn Ninh, KS; Đặng Hữu On, PGS.PTS; Phan Ngọc Cừ, PTS; Trần Đình Khai, PGS.PTS; Nguyễn Đức Thu, KS; Hoàng Đình Toàn, KS; Phan Thiện Cơ, KS; Đinh Viết Đường, KS; Phạm Quốc Tường, KS -- Từ khóa: Cấp nước; Đô thị; Chiến lược; Nước sinh hoạt; Giếng khoan